Effectiveness of a bacteriophage YZU_PF006 in controlling dairy spoilage caused by Pseudomonas fluorescens - Lei Yuan; Lili Ma; Yang Liu; Xinhai Yuan; Shuo Wang; Wenyuan Zhou; Zhenbo Xu; Zhenquan Yang (Journal of Dairy Science)
ABSTRACT: Pseudomonas fluorescens is a psychrophilic bacterium that can cause dairy spoilage by producing heat-stable enzymes. Bacteriophages are proved as one of the alternatives to control spoilage bacteria in today's dairy industry. This study aimed to investigate how a previously identified phage YZU_PF006 prevents dairy spoilage caused by P. fluorescens. Results demonstrated that phage YZU_PF006 effectively controlled P. fluorescens growth and production of protease at 7°C and 28°C in milk in a phage concentration-dependent way. Phage YZU_PF006 at a multiplicity of infection (MOI) of 100 increased the pH values of milk by 1.43 at 28°C and 0.81 at 7°C, increased the particle size of milk by 2.74 μm at 28°C and 1.74 μm at 7°C. Phage YZU_PF006 reduced the free AA content by 15.36% at 28°C and 32.03% at 7°C, and decreased the contents of Glu (206.678 mmol/L at 28°C and 40.481 mmol/L at 7°C), Phe (94.137 mmol/L at 28°C and 144.137 mmol/L at 7°C) and other amino acids in milk. In contrast, high-throughput sequencing analysis revealed that phage YZU_PF006 specifically prevented the growth of Pseudomonas in raw milk at low temperatures. Results demonstrated that phage YZU_PF006 can be used alone or in combination with other control strategies to serve as one of the good antimicrobial candidates to control P. fluorescens contamination in dairy processing environments, and to promote the safety and sensory quality of raw milk and milk products.